Analysis of demagnetization fault back-EMF of permanent magnet synchronous motor using mathematical model based on magnetic field superposition principle - Zhiyan Zhang; Zehui Xie; Hongzhong Ma; Qin Zhong (Технічна електродинаміка, 2016)
According to magnetic field superposition principle and characteristic of square wave series, back-EMF of permanent magnet synchronous motor (PMSM) under demagnetization fault condition is decomposed into health component and demagnetization fault component. A operation of mathematical model of single slot and single phase no-load backEMF, when demagnetization fault of different degree occurred in any magnetic body, any single pole and any multiple pole, is presented. The back-EMF mathematical model and the finite element simulation model results for 42 kW - PMSM, which has 8 poles and V-shaped permanent magnet rotor structure are compared, that allowed to verify the mathematical model. The results show that the back-EMF waveform of the slot winding can reflect the specific position and the severity of the demagnetization poles. The single phase back-EMF waveform can reflect only demagnetization conditions of all poles, but can not identify the specific position of the demagnetization poles. В соответствии с принципом суперпозиции магнитного поля и характеристиками серий прямоугольных сигналов противодействующая электродвижущая сила синхронного двигателя с постоянными магнитами (СДПМ) в состоянии эффекта размагничивания раскладывается на рабочий компонент и компонент эффекта размагничивания. В статье представлена математическая модель однопазовой и однофазной противодействующей электродвижущей силы без нагрузки, когда при любом магнитном теле, любом полюсе или нескольких полюсах возникает эффект размагничивания. В статье сопоставлены результаты математической модели противодействующей электродвижущей силы СДПМ мощностью 42 кВт, который имеет 8 полюсов и V- образную форму постоянных магнитов, с результатами имитационного моделирования методом конечных элементов, что позволило подтвердить математическую модель. Результаты показывают, что форма сигнала противодействующей электродвижущей силы пазовой части обмотки может отражать определённое положение полюсов размагничивания. Форма сигнала однофазной противодействующей электродвижущей силы может отражать только условия размагничивания всех полюсов, но не может определять конкретное положение полюсов размагничивания. Відповідно до принципу суперпозиції магнітного поля і характеристик серій прямокутних сигналів протидіюча електрорушійна сила синхронного двигуна з постійними магнітами (СДПМ) у стані ефекту розмагнічування розкладається на робочий компонент і компонент ефекту розмагнічування. У статті представлено математичну модель однопазової та однофазної протидіючої електрорушійної сили без навантаження, коли при будьякому магнітному тілі, будь-якому одному або при декількох полюсах виникає ефект розмагнічування. У статті співставлено результати математичної моделі протидіючої електрорушійної сили СДПМ потужністю 42 кВт, який має 8 полюсів та V-подібну форму постійних магнітів, з результатами моделі для імітаційного моделювання методом кінцевих елементів, що дозволило перевірити і підтвердити математичну модель. Результати показують, що форма сигналу протидіючої електрорушійної сили пазової частини обмотки може відображати певне положення полюсів розмагнічування. Форма сигналу однофазної протидіючої електрорушійної сили може відображати тільки умови розмагнічування всіх полюсів, проте не може визначати конкретне положення полюсів розмагнічування.